2004
DOI: 10.1002/1529-0131(199803)41:3<460::aid-art12>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of HLA-DR genes on susceptibility to and severity of ankylosing spondylitis

Abstract: Objective. To analyze the effect of HLA-DR genes on susceptibility to and severity of ankylosing spondylitis (AS).Methods. Three hundred sixty-three white British AS patients were studied; 149 were carefully assessed for a range of clinical manifestations, and disease severity was assessed using a structured questionnaire. Limited HLA class I typing and complete HLA-DR typing were performed using DNA-based methods. HLA data from 13,634 healthy white British bone marrow donors were used for comparison.Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 27 publications
1
34
2
Order By: Relevance
“…This might lead some to postulate that HLA-DRB1 forms a separate locus for AS predisposition. Other studies have suggested this (6). However, the tight linkage disequilibrium known to exist between MHC genes makes it impossible to assign a definite and dominant role for any 1 MHC locus in this study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…This might lead some to postulate that HLA-DRB1 forms a separate locus for AS predisposition. Other studies have suggested this (6). However, the tight linkage disequilibrium known to exist between MHC genes makes it impossible to assign a definite and dominant role for any 1 MHC locus in this study.…”
Section: Discussionmentioning
confidence: 64%
“…Although the MHC is likely the primary mediator of genetic susceptibility to AS, it explains Ͻ50% of the total genetic risk for AS (6,7). Genome-wide linkage scans have implicated numerous non-MHC genomic regions, including 1p, 2p, 2q, 3p, 9q, 10q, 11p, 19q, and 16q (9,10).…”
mentioning
confidence: 99%
“…Finally, the specificity of the staining also could not be completely explained by the presence of the SE in RA. Indeed, half of the control patients who were tested for HLA-DR turned out to be SE positive, especially in the group with SpA (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…66 HLA-B60 shows association with both B27-positive and negative AS, and this association has been replicated in a Chinese population. 67 The MHC class II gene HLA-DRB1 has been found to be associated with AS in B27 matched case control studies 68 and twin studies. 12 A study of non-B27 MHC associations of AS using B27-matched haplotypes in cases and controls has shown that HLA-DRB1 is associated with AS irrespective of whether the haplotype contained HLA-B27.…”
Section: Other Mhc Genesmentioning
confidence: 99%